2015
DOI: 10.1002/app.42799
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of melamine formaldehyde fibers for decontaminating biological and chemical warfare agents

Abstract: The demand for protection against biological and chemical warfare agents has increased the need for unique protective materials. N-halamines are superior candidates for this task by having rapid inactivation rates against a broad range of microorganisms and the ability to oxidize some pesticides and warfare agents to reduce their toxicity to humans. Thus, the design of N-halamine materials having fibrous structure, high halogen loading capacity with enhanced stability, and being relatively inexpensive is very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Melamine formaldehyde (MF) fibers have also been used to obtain new melamine-containing N-halamines. Kocer et al 191 reported that to prepare melamine-containing N-halamines, they used melamine formaldehyde (MF) fibers in a hydrolysis reaction with sulfuric acid aqueous solution, followed by chlorination with household bleach. They found that when some of the formaldehyde had been released from the fibers after acid treatment, the fibers became more accessible to chlorine absorption.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Melamine formaldehyde (MF) fibers have also been used to obtain new melamine-containing N-halamines. Kocer et al 191 reported that to prepare melamine-containing N-halamines, they used melamine formaldehyde (MF) fibers in a hydrolysis reaction with sulfuric acid aqueous solution, followed by chlorination with household bleach. They found that when some of the formaldehyde had been released from the fibers after acid treatment, the fibers became more accessible to chlorine absorption.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The biocidal performance of the hydrolyzed chlorinated-treated fibers was further improved by a hydrophilic N-halamine surface coating. 191 2.2.7. Polysaccharide-Containing N-Halamines.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 3 more Smart Citations